Modifikasi Iklim Mikro Hijauan dan pengaruhnya terhadap Kandungan Gula Total dan Serat Kasar - Mappaona .; Soedarmadi Hardjosuwignjo; I. Kismono (Buletin Ilmu Makanan Ternak, 1988)
Modification of forage micro climate and its influence on the total sugar and crude fibre content of herbage. In order to obtain information the influence of shading intensity and nitrogen application on the total sugar and crude fibre content of the herbage, a split-plot experiment was conducted at IPB experimental farm, at tajur from April to august, 1986. The result showed that shading did not affect the total sugar content in the first cutting and the crude fibre content in the first and second cuttings, but affected the total sugar content of the herbage at the second cutting.Nitrogen did not affect both the total sugar and crude fibre content of the herbage. However, there is interaction between shading and nitrogen on the crude fibre content at the second cutting; At 30% intensity, the higher the nitrogen applied the lower the crude fibre content of the herbage.